Nature's Calendar - phenological observations made by Citizen Scientists - Nature's calendar - Beekeeper's Calendar - Langvall, Ola; Dahl, Åslög; Bolmgren, Kjell; Swedish Beekeepers Association (Swedish University of Agricultural Sciences, 2022)
Nature's Calendar (www.naturenskalender.se, in Swedish only) is run by the Swedish National Phenology Network, a consortium of Swedish universities, governmental agencies and NGO:s. The Swedish University of Agricultural Sciences hosts the network. The main task for the Nature's calendar is to collect observations of different spring and autumn signs appearing during the vegetation season.

Data about the nature's calendar is collected in two ways, the long-term environmental monitoring through "Calendars", where phenological observations are reported all through the year, and through "Checks", where phenology observations are reported during short-time campaigns, giving a snapshot of the phenological status at a certain time of the year.

Calendars
The long-term environmental monitoring is performed by citizen scientists and professional observers at research stations and like. Three calendars have been launched in the Nature's Calendar; the Plant's Calendar (from 2008), the Bird's Calendar (from 2016) and the Beekeeper's Calendar (between 2015 and 2018).

Checks
Starting in 2015, a campaign called "Vårkollen" (i.e. "Spring Check") has been run during two (April 30 - May 1) or three (April 29 - May 1) days every year. The campaign, where the phenology of only 6 species (also available in the historical phenology dataset) gives a snapshot of how spring has proceeded all over the country at this time.

Aims
Phenological changes in nature gives the most obvious signs of the biological effect of climate change. Spring signs, autumn signs, the start, end and length of the growing season, and many other signs in nature are basic properties of ecosystems. Also, the interaction between different organisms, e.g. flowering plants and pollinators, are affected if the nature's calendar changes. Observations reported to the Nature's Calendar can be compared to similar observations collected for more than 100 years ago (see Swedish Historical Phenology Dataset, published in another place at this platform), to detect evidence of phenological shifts over time that can be connected to climate change.

The aim of the Nature's Calendar is to collect phenological data from the first spring sign to the last autumn sign, to be able to offer nation-wide data to everyone interested, to facilitate research, environmental assessments, the evaluation of environmental goals, etc, to be better prepared to meet the effects of climate change. For example, the data collected in Nature's Calendar is continuously used to evaluate the Swedish environmental objective Reduced Climate through the indicator called ”Growing Season” (www.slu.se/vaxternasvaxtsasong).

Three datasets are made available in this publication: the Plant's Calendar, the Beekeeper's Calendar and the Spring Check datasets. They all originate from the same database in the Nature's Calendar, while the Bird's Calendar observations are published through the Swedish Species Observation System Portal (www.artportalen.se).

In the Beekeeper's Calendar, Citizen Scientists have reported observations of how
- flowering of plants
- bees and bumblebees flights
- living status of the colony
- supplemental feeding
- angel ball status
- honey production
- tax box additions
- presence of varroa mite
have developed during the growing season.

The aim with the data collection is to obtain nationwide data that can provide information to understand, track changes and predict effects of climate change on beekeeping in Sweden.

The dataset includes one file with observation data (beekeepers_calendar_2015-2021.csv), one PDF file (metadata_beekeepers_calendar_2015-2021.pdf) with metadata that describes how the included parameters should be interpreted and lists of included species and phases, and one PDF file (bikalendern_fenologimanual_2015.pdf) which is the instruction given to the observers (in Swedish, only). The observation data file includes totally 1 948 observations, which are specific for the Beekeeper's Calendar.

The observation data file could be used as is, while the other files are supporting material for the understanding of the observation data file. As this dataset only includes observations made of the activities in the bee hive, the dataset "Nature's Calendar - Plant's Calendar", found as a separate dataset in this publication, is also needed, to be able to fully evaluate this dataset, especially when analyzing interactions between the timing of flowering of plants in the vicinity and the activities in the bee hive.

The Beekeeper's Calendar was actively carried out during the years 2015-2018, but reports from bee keepers have been collected until 2021, which have also been included in this dataset.

Coordinates of the observation locations have been made diffuse, to make it impossible to trace back the observations to the observer (coordinates are rounded to 3 decimals).

Naturens kalender (www.naturenskalender.se) drivs av Svenska fenologinätverket, som är ett nätverk med flera universitet, myndigheter och föreningar. SLU, Sveriges lantbruksuniversitet, är nätverkets huvudman.
Huvuduppgiften för Naturens kalender är att samla in observationer av vårtecken, hösttecken och annat i naturens kalender.

Data om naturens kalender samlas in på två olika sätt. Dels bedrivs en långsiktig miljöövervakning i form av ”kalendrar” där rapporter om fenologiska observationer samlas in över hela året, dels genomför vi korta ”kollar” där vi tar en ögonblicksbild av naturens kalender i landet vid en viss tidpunkt på året.

Kalendrar
Den långsiktiga miljöövervakningen genomförs av frivilliga och professionella medborgarforskare, s.k. fenologiväktare, i Växtkalendern (från 2008) och Fågelkalendern (från 2016). Under åren 2015-2018 fanns också Bikalendern, som förutom att samla in observationer av växters fenologi, också registrerade aktiviteter som biodlare utförde på bigården som beskriver binas aktiviteter och skötsel.

Kollar
Med början 2015 genomförs Vårkollen under Valborgshelgen, en 2-dagars (30/4-1/5) eller 3-dagars (29/4-1/5) kampanj där vi med hjälp av medborgarforskares observationer från hela landet får en "ögonblicksbild" av hur långt våren kommit vid den tidpunkten. I Vårkollen samlas enbart fenologiska observationer på 6 arter, vilka även förekommer i det historiska datasetet, in.

Motiv och syfte
Fenologiska förändringar i naturen är den tydligaste biologiska effekten av en klimatförändring. Vårtecken, hösttecken, växtsäsongens start, slut, längd och andra händelser i naturens kalender är kopplade till grundläggande egenskaper hos ekosystemen. Samspelet mellan olika arter, t.ex. växterna och deras pollinatörer, påverkas också, om naturens kalender ändras. En förändring av naturens kalender får också effekt för landets alla pollenallergiker eftersom både tidpunkten och längden på pollenperioden ändras. Observationer som samlas in i Naturens kalender kan jämföras med motsvarande observationer som gjordes för över 100 år sedan (se Svenskt historiskt fenologidataset, som publicerats på annan plats på SND), för att upptäcka fenologiska förändringar över tid som kan bero på klimatförändringar.

Målet med Naturens kalender är att samla in data om allt från första vårtecken till sista hösttecken, så att vi kan erbjuda landsomfattande data till alla intresserade, för att underlätta forskning, miljömålsarbete och information och göra oss bättre rustade att möta klimatförändringens effekter. Data från Naturens kalender används exempelvis till uppföljningen av de svenska miljömålen genom miljömålsindikatorn ”Växternas växtsäsong” (www.slu.se/vaxternasvaxtsasong).

Här tillgängliggörs tre dataset: Växtkalendern, Bikalendern och Vårkollen, som alla kommer från samma databas i Naturens kalender. Fågelkalenderns data publiceras i Artportalen (www.artportalen.se).

I Bikalendern har medborgarforskare rapporterat in observationer av hur
- dragande växters blomning
- bin och humlors drag
- levandestatus på bisamhället
- stödutfodring
- yngelklot
- honungsproduktion
- skattlådor
- förekomst av varroa-kvalster
har utvecklats under säsongen.

Målet är att bidra med landsomfattande data för att bättre kunna följa, förstå och förutse klimatförändringens effekter på biodling i Sverige.

Datasetet innehåller en fil med observationsdata (beekeepers_calendar_2015-2021.csv), en PDF-fil (metadata_beekeepers_calendar_2015-2021.pdf) med metadata som beskriver ingående variabler och listor på ingående arter och faser, samt en PDF-fil (bikalendern_fenologimanual_2015.pdf), som är den instruktion som de som rapporterar kan läsa. Observationsdatafilen innehåller totalt 1 948 observationer specifika för bikalendern.

Observationsdatafilen kan användas fristående, övriga kan ses som kompletterande information för att förstå innehållet i denna (liksom att få fenologiska faserna i engelsk översättning). OBS! Datasetet Naturens kalender - Bikalendern innehåller enbart uppgifter som är specifikt för biodlingen. För att kunna studera interaktionen mellan aktiviteterna i bikupan och dragande växters fenologi, behövs även datasetet "Naturens kalender - Växtkalendern", som finns som ett separat dataset i denna publikation.

Bikalendern drevs aktivt under åren 2015-2018, men datainsamlingen har pågått fram till 2021, vilket ingår i detta dataset.

Koordinaterna för observationsplatserna har gjorts diffusa för att ta bort möjligheten att spåra observatören (avrundning till 3 decimaler).
Naturens kalender - fenologiska observationer av medborgarforskare - Naturens kalender - Bikalendern
Keywords: bee; bin; citizen science; medborgarforskning; Spring sign; Vårtecken; phenology; fenologi; Climate Science; Klimatvetenskap; Environmental Sciences; Miljövetenskap; Ecology; Ekologi; Biota; Biologi och ekologi